Structure-semantical typology of segmental constructions nominative of elucidatory-explanatory matter as expressive units (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article we study one of the variety of segmental constructions nominative of elucidatory-explanatory matter – nominative of attributive description. Structure-contextual types of this constructions peculiar for newspaper language are distinguished.
Keywords: segmental construction; nominative of elucidatory-explanatory matter; nominative of attributive description